Answer:
y=-2x+1
Step-by-step explanation:
y=Mx+b is the slope formula. You want to move y over to the other side to get the equation equal to y
Answer- 30
Step-by-step explanation:
Step-by-step explanation:
if there is no typo, then that is
y = 1 + 5 = 6
y = 6
has no term in x.
that means 6 is the constant result of the line function, no matter what x value we pick.
and that means this is a horizontal line (parallel to the x-axis) going through the point y=6 or (0, 6).
remember that the slope is the ratio "y coordinate change / x coordinate change".
but y is not changing at all, the change or difference is always 0 no matter what points we pick on the line.
and so, the slope ratio is always "0/...". and that is 0.
so, the slope of that line is 0.
but if there is a typo, then please know : the slope of a line
y =ax + b
is always a (the factor of x).
first is 86
we know because of the sum of the interior angles of a triangle being 180, and that 5 + 6 =180
Question 14, Part (i)
Focus on quadrilateral ABCD. The interior angles add to 360 (this is true for any quadrilateral), so,
A+B+C+D = 360
A+90+C+90 = 360
A+C+180 = 360
A+C = 360-180
A+C = 180
Since angles A and C add to 180, this shows they are supplementary. This is the same as saying angles 2 and 3 are supplementary.
==================================================
Question 14, Part (ii)
Let
x = measure of angle 1
y = measure of angle 2
z = measure of angle 3
Back in part (i) above, we showed that y + z = 180
Note that angles 1 and 2 are adjacent to form a straight line, so we can say
x+y = 180
-------
We have the two equations x+y = 180 and y+z = 180 to form this system of equations
![\begin{cases}x+y = 180\\y+z = 180\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Dx%2By%20%3D%20180%5C%5Cy%2Bz%20%3D%20180%5Cend%7Bcases%7D)
Which is really the same as this system
![\begin{cases}x+y+0 = 180\\0+y+z = 180\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Dx%2By%2B0%20%3D%20180%5C%5C0%2By%2Bz%20%3D%20180%5Cend%7Bcases%7D)
The 0s help align the y terms up. Subtracting straight down leads to the equation x-z = 0 and we can solve to get x = z. Therefore showing that angle 1 and angle 3 are congruent. We could also use the substitution rule to end up with x = z as well.